Hidden truth: A battle within individuals - Uganda Women’s Network (Uganda Women’s Network, 2013)
Sexual violence takes place within a variety of settings, including the home, the work place, schools and community. In many cases, it begins in childhood or adolescence. Sexual violence has a significant negative impact on the health of the population. The potential productive and sexual health consequences are numerous, i.e. Unwanted pregnancy, sexually transmitted infections (STIs), immunodeficiency virus/ acquired immunodeficiency syndrome (HIV/AIDs) and increased risk for adaptation of risky sexual behaviors (e.g. early and increased sexual involvement, and exposure to older and multiple partners). The mental health consequences of sexual violence can be just as serious and long lasting.